"THE INFLUENCE OF APIP COMPETENCE, INDEPENDENCE AND TIME BUDGET PRESSURE ON AUDIT QUALITY IN THE PUBLIC SECTOR: A CASE STUDY IN EAST LUWU REGENCY" - Suhaeni; Rismawati; Imam Pribadi; Muhammad Aqsa, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study analyzes the factors that affect the quality of public sector audits, focusing on APIP Competencies (X1), Independence (X2), and Time Budget Pressure (X3). Data was collected through a questionnaire distributed to auditors in East Luwu Regency and analyzed using path analysis. The results showed that Independence had the most significant influence on audit quality (path coefficient = 0.520; p = 0.000), followed by Competency (path coefficient = 0.389; p = 0.010). In contrast, Time Budget Pressure had an insignificant negative effect on audit quality (path coefficient = -0.149; p = 0.111). The novelty of this research lies in emphasizing the importance of independence and competence of auditors in the context of Indonesia's public sector, especially in East Luwu, as well as time management in the implementation of audits.